Hubungan Budaya Organisasi Dengan Profesionalisme Pegawai di Kantor Kecamatan Tellulimpoe Kabupaten Sinjai - Kasmawati, Kasmawati; Setiawati, Budi; Mustari, Nuryanti (Universitas Muhammadiyah Makassar, 2020)
The study aimed to find out how much the relationship between organizational culture and employee professionalism at the Tellulimpoe District Office in Sinjai Regency This study used quantitative with descriptive research type. These quantitative descriptive studies were methods for testing certain theories by examining the relationships between variables. The population and sample in this study were 35 people. Data collection techniques used questionnaire, observation, and documentation. The results of this study showed that the calculated value was greater than rtable (0.992 0.344). Therefore, there was a very strong relationship to organizational culture and employee professionalism in the Tellulimpoe District Office in Sinjai District.